Prawnoadministracyjne instrumenty ochrony przedsiębiorców narażonych na stosowanie praktyk monopolistycznych przysługujące Prezesowi Urzędu Transportu Kolejowego — uwagi na gruncie obowiązujących i projektowanych przepisów prawa - Małecka, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The goal of the paper is to analyse the applicable and designed regulations regarding legal-administrative instruments of protecting entrepreneurs exposed to monopolistic practices available to the President of the Office of Rail Transport. The regulations of the Act of 28th March 2003 on rail transport (consolidated text, Journal of Laws 2019, item 710) set the following tasks for the President of the Office of Rail Transport: supervision over fair and non-discriminating treatment of all applicants by managers in relation to the access to rail infrastructure and supervision over fair and non-discriminating treatment of all railway carriers in relation to the access to service infrastructure objects by operators of a service infrastructure object. Currently, two projects of amendments of the rail transport law extending the catalogue of tasks of the President of the Office of Rail Transport are underway.
Keywords: President of the Office of Rail Transport; monopolistic practices; rail transport